Measurements of Iceberg Melt Rates Using High‐Resolution GPS and Iceberg Surface Scans. Issue 3 (11th February 2021) - Schild, Kristin M.; Sutherland, David A.; Elosegui, Pedro; Duncan, Daniel
Abstract: Increasing freshwater input to the subpolar North Atlantic through iceberg melting can influence fjord‐scale to basin‐scale ocean circulation. However, the magnitude, timing, and distribution of this freshwater have been challenging to quantify due to minimal direct observations of subsurface iceberg geometry and melt rates. Here we present novel in situ methods capturing iceberg change at high‐temporal and ‐spatial resolution using four high‐precision GPS units deployed on two large icebergs (>500 m length). In combination with measurements of surface and subsurface geometry, we calculate iceberg melt rates between 0.10 and 0.27 m/d over the 9‐day survey. These melt rates are lower than those proposed in previous studies, likely due to using individual subsurface iceberg geometries in calculations. In combining these new measurements of iceberg geometry and melt rate with the broad spatial coverage of remote sensing, we can better predict the impact of increasing freshwater injection from the Greenland Ice Sheet. Plain Language Summary: The acceleration of Greenland glaciers has led to an increase of icebergs discharged in nearby waters. As icebergs melt, they release freshwater into salty ocean waters, impacting local circulation. In order to understand how global circulation will change in the future, we need accurate iceberg melt rates. To do this, we use measurements of mass loss from on‐iceberg GPS units, and three‐dimensional iceberg geometry constructed from aerial drone and subsurface sonar data. We found melt rates smaller than previous studies and strong evidence for variable overall melt rates with different keel depths and over time. This study is the first of its kind to calculate melt rates using exact iceberg geometry. To better predict iceberg impacts, future iceberg studies should take these geometry results into account. Key Points: High resolution on‐iceberg GPS units show temporally variable melt rate over the 9‐day survey period Contrasting melt rates between different sized icebergs supports the hypothesis of depth‐variable melt rates Melt rates are lower than prior studies, likely due to using observed subsurface geometry (not idealized or end‐member) in calculations